Positive electrode active material, preparation method thereof and lithium secondary battery containing the same

By covering the surface of lithium metal oxide particles with boron compound coating of lithium ion conductive material to form a secondary particle structure, the problem of insufficient output characteristics of lithium secondary batteries is solved, and higher output characteristics and thermal stability are achieved.

CN114556633BActive Publication Date: 2025-03-18POHANG IRON & STEEL CO LTD +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202080072170.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-08-22
Filing Date
2020-08-13
Publication Date
2025-03-18
Estimated Expiration
2040-08-13

AI Technical Summary

Technical Problem

The output characteristics of existing lithium secondary batteries are insufficient and it is difficult to meet the high output requirements.

Method used

By coating the boron compound of the lithium ion conductive material on the surface of the lithium metal oxide particles, a secondary particle structure is formed, thereby improving the output characteristics of the lithium secondary battery.

Benefits of technology

It significantly improves the output characteristics and thermal stability of lithium secondary batteries, extends the high-temperature life and improves the high-temperature increase rate characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114556633B_ABST
    Figure CN114556633B_ABST
Patent Text Reader

Abstract

The present embodiment relates to a positive electrode active material, a preparation method thereof, and a lithium secondary battery comprising the positive electrode active material. According to one embodiment, the positive electrode active material is a lithium metal oxide particle in the form of a secondary particle comprising a primary particle, a coating containing a boron compound is located on at least a portion of the surface of the primary particle, and the boron compound may include an amorphous structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode active material, a preparation method thereof and a lithium secondary battery comprising the same. Background Art

[0002] In recent years, with the explosive growth in demand for IT mobile devices and small electric drive devices (electric bicycles, small EVs, etc.) and the increasing demand for electric vehicles with a range of more than 400 km, research and development of secondary batteries with high capacity and high energy density are actively carried out worldwide.

[0003] For electric vehicles, high output characteristics related to rapid acceleration are particularly important. Conventionally, in order to manufacture such high-output batteries, research has mainly been conducted to improve the performance of negative electrode active materials, but recently research has also been active on improving the output characteristics of positive electrode active materials. Summary of the invention

[0004] Technical issues

[0005] This embodiment aims to provide a positive electrode active material, which can greatly improve the output characteristics of a lithium secondary battery by coating a lithium ion conductive material on the surface of primary particles.

[0006] Technical Solution

[0007] According to an embodiment of the positive electrode active material, which is a lithium metal oxide particle in the form of a secondary particle including a primary particle, a coating layer containing a boron compound is located on at least a portion of a surface of the primary particle, and the boron compound may include an amorphous structure.

[0008] According to another embodiment, a method for preparing a positive electrode active material comprises: a step of preparing a coating-forming substance containing a boron compound; a step of adding a metal salt aqueous solution into a co-precipitation reactor to obtain a metal precursor; and a step of mixing the coating-forming substance, the metal precursor and a lithium raw material and then calcining them to obtain a positive electrode active material. The average particle size of the coating-forming substance containing a boron compound may be 0.3 μm to 1 μm.

[0009] Effects of the Invention

[0010] According to the positive electrode active material of this embodiment, the coating layer of the boron-containing compound having lithium ion conductivity is located on the surface of the primary particles, so the output characteristics of the lithium secondary battery using the positive electrode active material can be greatly improved.

[0011] Meanwhile, according to the present embodiment, since the particle strength of the positive electrode active material is increased, the side reaction with the electrolyte can be suppressed, thereby improving the thermal stability, thereby significantly improving the high temperature life and high temperature increase rate characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 is a partial schematic diagram of a secondary particle according to one embodiment of the present invention.

[0013] Figure 2 The XRD detection result of Li3BO3, an example of the boron compound forming the coating, is shown.

[0014] Figure 3a The cross-sectional analysis results of the positive electrode active material prepared in Example 1 are shown.

[0015] Figure 3b Show Figure 3a EELS analysis results of the primary particle surface.

[0016] Figure 3c Zoom in to show Figure 3b Part of the spectrum in the mid-boron detection region.

[0017] Figure 4a The cross-sectional analysis results of the positive electrode active material prepared in Comparative Example 4 are shown.

[0018] Figure 4b Show Figure 4a EELS analysis results of the primary particle surface.

[0019] Figure 5 The average particle size analysis result of the positive electrode active material of Comparative Example 1 is shown.

[0020] Figure 6 The average particle size analysis results of the positive electrode active material of Example 1 are shown.

[0021] Figure 7 The particle strength test results of the positive electrode active material of Example 1 are shown.

[0022] Figure 8 The particle strength test results of the positive electrode active material of Comparative Example 1 are shown.

[0023] Fig. 9 A graph comparing initial charge and discharge after charging and discharging is shown for the positive electrode active materials of Example 1 and Comparative Example 1 after the charge voltage is increased to 4.5 V.

[0024] Fig.10 The results of testing the high temperature life characteristics of the positive electrode active materials of Example 1 and Comparative Example 1 are shown.

[0025] Fig.11 The results of measuring the high-temperature resistance increase rate of the positive electrode active materials of Example 1 and Comparative Example 1 are shown.

[0026] Fig.12aThe TEM structural analysis results of the primary particle surfaces of the positive electrode active material prepared according to Example 1 are shown.

[0027] Figure 12b Zoom in to show Fig.12a The TEM analysis results show a region where primary particles of a positive electrode active material and a coating layer located on the surface of the primary particles coexist. DETAILED DESCRIPTION

[0028] Hereinafter, embodiments of the present invention will be described in detail. However, the following embodiments are examples only, and the present invention is not limited to the embodiments described herein, and the scope of the present invention is subject to the claims.

[0029] According to an embodiment of the positive electrode active material, which is a lithium metal oxide particle in the form of a secondary particle including a primary particle, a coating layer containing a boron compound may be located on at least a portion of a surface of the primary particle.

[0030] The boron compound may include an amorphous structure. For the positive electrode active material of this embodiment, the coating layer of the boron compound including the amorphous structure as described above is located on the surface of the lithium metal oxide particles, thereby increasing the particle strength and reducing the porosity.

[0031] The particle strength of the large lithium metal oxide particles may be 151MPa to 200MPa, more specifically 160MPa to 195MPa or 170MPa to 190MPa. When the particle strength of the lithium metal oxide meets the range, the secondary particles have a dense structure and low porosity. In the present embodiment, since the coating of the boron-containing compound is located on at least a portion of the surface of the primary particles, the structure of the particles is dense, and lithium ions are also easily migrated inside the secondary particles (i.e., between the primary particles), so the discharge capacity can be increased once, and a lithium secondary battery with high output characteristics can be realized. In addition, when the particle strength of the lithium metal oxide meets the range, cracks can be suppressed in the charging and discharging of the lithium secondary battery, thereby suppressing side reactions with the electrolyte, and further improving the life characteristics.

[0032] On the other hand, the porosity of the lithium metal oxide particles may be 0.3% to 7%, and more specifically 0.4% to 6% or 0.6% to 5.6%.

[0033] The porosity of the lithium metal oxide particles can be detected by the following method and can be expressed as the following formula 1.

[0034] For example, the porosity can be calculated by cutting the center of a lithium metal oxide particle by a method such as FIB (focused ion beam) milling and then detecting the pores in the lithium metal oxide particle by area using a scanning electron microscope (SEM).

[0035] [Formula 1]

[0036] Porosity (%) = (pore area of ​​lithium metal oxide particle cross section A / area of ​​lithium metal oxide particle cross section A) × 100

[0037] In Formula 1, A represents the area of ​​a cross section having a diameter of a lithium metal oxide particle.

[0038] In this embodiment, the coating containing the boron compound as described above is located on at least a portion of the primary particles, so that the output characteristics of the positive electrode active material can be greatly improved. This is because the boron compound forms a path for lithium ions to migrate through the boundary between the primary particles. In addition, by filling the gaps between the primary particles, the porosity of the particles can be reduced, thereby improving the output characteristics.

[0039] On the other hand, the average particle size (D50) of the primary particles may be increased by 1.3 to 2.5 times compared to the case where the coating layer containing the boron compound is not located on at least a portion of the surface of the primary particles after calcination at the same calcination temperature.

[0040] More specifically, the average particle diameter (D50) of the primary particles may be 0.3 μm to 2 μm, and further specifically 0.4 μm to 1.5 μm or 0.5 μm to 1.3 μm.

[0041] As described above, the average particle size (D50) of the primary particles increases, and when the range is met, the crystallinity of the secondary particles increases. Thus, when the crystallinity increases, it is beneficial for the deintercalation / intercalation of lithium ions, and the life characteristics can be improved. In addition, the residual lithium content on the surface of the positive electrode active material can be reduced, which is very beneficial.

[0042] In the positive electrode active material of the present embodiment, the lithium metal oxide particles may be plural. More specifically, the lithium metal oxide particles may be at least one of large particles having an average particle size (D50) of 10 μm to 30 μm, small particles having an average particle size (D50) of 1 μm to 6 μm, and bimodal particles in which the large particles and the small particles are mixed together.

[0043] For example, the average particle size (D50) of the large particles may be 10 μm to 30 μm or 12 μm to 20 μm. For example, the average particle size (D50) of the small particles may be 1 μm to 6 μm or 2 μm to 5 μm. In addition, for example, the bimodal particles may be the large particles and the small particles mixed together in a weight ratio of 5:5 to 9:1 or 6:4 to 8:2.

[0044] In this embodiment, the half maximum width FWHM of the diffraction peak of the (110) plane of the large particle based on X-ray diffraction is (110) It may be 0.14° to 0.18°. In addition, the half maximum width FWHM of the diffraction peak of the (110) plane of the small particles based on X-ray diffraction is (110) It can be 0.15° to 0.19°. When the FWHM of the (110) plane of the large particle and the small particle (110) When the above range is satisfied, the positive electrode active material can exhibit excellent crystallinity. Therefore, the positive electrode active material of this embodiment has a stable structure and has an advantage of having very excellent life characteristics when applied to a lithium secondary battery.

[0045] On the other hand, for example, the boron compound contained in the coating layer located on at least a portion of the surface of the primary particle may be Li3BO3, LiBO2, Li3B3O5, Li6B4O9, Li 6.52 B 18 O 0.7 , Li 7.4 B 18 O 0.7 , Li 7.8 B 18 O 0.9 and at least one of Li2B4O7. In particular, in the present embodiment, when the boron compound is Li3BO3, it has excellent ion conductivity, does not react with lithium byproducts, and can effectively diffuse to the surface of the primary particles of the positive electrode active material to form a coating.

[0046] Secondly, the content of the boron compound in the secondary particles may be 0.001 mol to 0.01 mol, more specifically 0.003 to 0.005 mol or 0.004 to 0.006 mol. If the content of the boron compound contained in the secondary particles is less than 0.001 mol, a coating will not be effectively formed on the surface of the primary particles, and there is a problem of not being able to improve the performance of the positive electrode active material. In addition, if the content of the boron compound is greater than 0.01 mol, too much coating will be formed on the surface of the primary particles, so there is a problem of reduced output and life characteristics.

[0047] The nickel content of the metal in the secondary particles may be 0.65 mol to 0.99 mol, more specifically 0.65 mol to 0.92 mol or 0.7 mol to 0.91 mol. Thus, when the nickel content is 0.65 mol or more, high output characteristics that cannot be obtained in a positive electrode active material having a nickel content of 0.5 mol or less can be achieved.

[0048] More specifically, for example, the lithium metal oxide may be represented by Chemical Formula 1 below.

[0049] [Chemical formula 1]

[0050] Li x Ni a Co b Mn c M d M2 e O2

[0051] In Chemical Formula 1, M1 and M2 are each at least one of Zr, Ti, Mg, Al, Ni, Mn, Zn, Fe, Cr, Mo and W, x is 0.90≤x≤1.07, a is 0.65≤a≤0.99, b is 0<b≤0.3, c is 0<c≤0.3, d is 0<d<0.01, e is 0<e<0.01, and a+b+c+d+e=1.

[0052] At this time, b may be 0<b≤0.2 or 0<b≤0.1, and c may be 0<c≤0.2 or 0<c≤0.1.

[0053] Meanwhile, the M1 may be Zr, and the M2 may be Al. When M1 is Zr and M2 is Al, the positive electrode active material of this embodiment may include 0.05 to 0.6 parts by weight of Zr and 0.01 to 0.4 parts by weight of Al based on the total lithium metal oxide.

[0054] The positive electrode active material of this embodiment may further include a surface layer located on the surface of the secondary particles. For example, the surface layer may include one or more selected from the group consisting of B, Zr, Al, W, Nb, P, Ce, Ti, Ta, Co, Si and Mn. Thus, when the surface layer located on the surface of the secondary particles is further included, the side reaction between the positive electrode active material and the electrolyte can be suppressed, thereby significantly reducing the degradation of the lithium secondary battery.

[0055] In another embodiment of the present invention, a method for preparing a positive electrode active material is provided, which comprises: a step of preparing a coating-forming substance; a step of adding a metal salt aqueous solution into a coprecipitation reactor to obtain a metal precursor; and a step of mixing the coating-forming substance, the metal precursor and a lithium raw material and then calcining them to obtain a positive electrode active material.

[0056] In particular, in this embodiment, the coating forming substance may be provided in the form of micro-particle powder. For example, the average particle size (D50) of the micro-particle powder may be 0.1 μm to 1.5 μm, more specifically 0.3 μm to 1 μm.

[0057] More specifically, the step of preparing the coating-forming substance includes the steps of mixing the raw materials constituting the boron compound and then calcining the mixture, and pulverizing the calcined mixture. At this time, for example, the step of mixing the raw materials constituting the boron compound and then calcining the mixture can be performed at a temperature range of 400° C. to 700° C. for 2 to 7 hours. When calcining is performed under the above conditions, there is an advantage that a lithium ion conductor in which lithium ions can easily migrate can be effectively prepared.

[0058] As described above, when the coating-forming substance is prepared in the form of solid microparticles and then mixed with a metal precursor and a lithium raw material to prepare a positive electrode active material, the boron compound penetrates into the interior of the secondary particles, more specifically, into the surface of the primary particles, thereby forming a coating.

[0059] Figure 1 A partial schematic diagram showing a secondary particle according to one embodiment of the present invention.

[0060] See also Figure 1 As described in this embodiment, when the coating-forming substance is prepared in the form of solid microparticles and then mixed with a metal precursor and a lithium raw material to prepare a positive electrode active material, the boron compound can penetrate into the surface of the primary particles, that is, between the interfaces between the primary particles. Therefore, the boron compound with high lithium ion conductivity exists between the interfaces of the primary particles, thereby greatly improving the output characteristics of the positive electrode active material.

[0061] On the other hand, more specifically, the step of obtaining the positive electrode active material may also include: mixing the coating forming substance, the metal precursor and the lithium raw material, calcining to prepare a calcined body, washing it with water, and forming a surface layer on the calcined body after washing.

[0062] The water washing step is to remove residual lithium on the surface, and can be performed by, for example, using distilled water.

[0063] Next, the washed calcined body may be dried to remove moisture, etc. For example, the drying may be performed at a temperature ranging from 80° C. to 300° C. for 1 hour to 30 hours.

[0064] Next, a step of forming a surface layer on the dried calcined body may be performed.

[0065] Specifically, the step of forming a surface layer covering the outer surface of the lithium metal oxide particles may include the steps of mixing the lithium metal oxide particles and a raw material material for forming the surface layer to prepare a mixture and heat-treating the mixture.

[0066] For example, the raw material for forming the surface layer may be one or more selected from the group consisting of B, Zr, Al, W, Nb, P, Ce, Ti, Ta, Co, Si and Mn. The step of mixing the lithium metal oxide particles and the raw material for forming the surface layer to prepare the mixture is not limited to dry mixing or wet mixing.

[0067] Next, for example, the heat treatment step may be performed at a temperature ranging from 200° C. to 800° C. in an air (Air), oxygen (O 2 ) or nitrogen (N 2 ) environment for 1 hour to 10 hours.

[0068] In the following examples, more detailed conditions for preparing the positive electrode active material of this example will be described in more detail.

[0069] In another embodiment of the present invention, a lithium secondary battery is provided, which includes: a positive electrode including the positive electrode active material according to one embodiment of the present invention; a negative electrode including the negative electrode active material; and an electrolyte located between the positive electrode and the negative electrode.

[0070] The description of the positive electrode active material is the same as that of the aforementioned embodiment of the present invention, and thus will not be repeated herein.

[0071] The positive active material layer may include a binder and a conductive material.

[0072] The binder plays a role in allowing the positive electrode active material particles to be well bonded to each other and allowing the positive electrode active material to be well bonded to the current collector.

[0073] The conductive material is used to impart conductivity to the electrode, and any conductive material may be used as long as it does not cause chemical changes in the constituted battery.

[0074] The negative electrode includes a current collector and a negative electrode active material layer formed on the current collector, wherein the negative electrode active material layer includes a negative electrode active material.

[0075] As the negative electrode active material, a substance capable of reversibly intercalating / deintercalating lithium ions, lithium metal, an alloy of lithium metal, a substance capable of doping and dedoping lithium, or a transition metal oxide may be used.

[0076] As the substance capable of reversibly inserting and extracting lithium ions, any carbon-based negative electrode active material generally used as a carbon substance in lithium ion secondary batteries can be used, and as a typical example thereof, crystalline carbon, amorphous carbon, or a combination thereof can be used.

[0077] As the alloy of the lithium metal, an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al and Sn can be used.

[0078] Examples of the substance capable of lithium doping and dedoping include Si, SiO x (0<x<2), Si-Y alloy (the Y is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements and combinations thereof, but not Si), Sn, SnO2, Sn-Y (the Y is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements and combinations thereof, but not Sn), etc.

[0079] Examples of the transition metal oxide include vanadium oxide, lithium vanadium oxide, etc. The negative electrode active material layer also includes a binder and may further include a conductive material.

[0080] The binder plays a role in allowing negative electrode active material particles to be well bonded to each other and allowing the negative electrode active material to be well bonded to the current collector.

[0081] The conductive material is used to impart conductivity to the electrode, and any conductive material may be used as long as it does not cause chemical changes in the constituted battery.

[0082] As the current collector, a material selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer material coated with a conductive metal, and a combination thereof may be used.

[0083] For the negative electrode and the positive electrode, an active material, a conductive material and a binder are mixed in a solvent to prepare an active material composition, and the composition is coated on a current collector to prepare the negative electrode and the positive electrode. Such an electrode preparation method is well known in the art, so a detailed description is omitted in this specification. As the solvent, N-methylpyrrolidone and the like can be used, but it is not limited thereto.

[0084] The electrolyte includes a nonaqueous organic solvent and a lithium salt.

[0085] The nonaqueous organic solvent functions as a medium through which ions participating in the electrochemical reaction of the battery can migrate.

[0086] The lithium salt is a material that functions as a lithium ion source in a battery when dissolved in an organic solvent, thereby ensuring the basic operation of a lithium secondary battery and promoting the migration of lithium ions between a positive electrode and a negative electrode.

[0087] Depending on the type of lithium secondary battery, a separator may also be present between the positive electrode and the negative electrode. As such a separator, polyethylene, polypropylene, polyvinylidene fluoride or a multilayer film of at least two layers thereof may be used, and of course mixed multilayer films such as polyethylene / polypropylene two-layer separators, polyethylene / polypropylene / polyethylene three-layer separators, polypropylene / polyethylene / polypropylene three-layer separators, etc. may be used.

[0088] For lithium secondary batteries, according to the types of separators and electrolytes used, they can be divided into lithium ion batteries, lithium ion polymer batteries and lithium polymer batteries. According to the shape, they can be divided into cylindrical, prismatic, coin and bag types. According to the size, they can be divided into block and film types. The structure and preparation method of these batteries are well known in the field, so they will not be described in detail.

[0089] Hereinafter, embodiments of the present invention will be described in detail. However, the following embodiments are merely examples, and the present invention is not limited to the following embodiments, and the scope of the present invention is subject to the claims.

[0090] (Preparation Example 1)—Preparation of coating-forming material and confirmation of properties

[0091] The raw materials LiOH·H2O and H3BO3 constituting the boron compound were weighed in a stoichiometric ratio, mixed, and then calcined at 600°C for 4 hours for synthesis.

[0092] Figure 2 The XRD test results of the coating-forming material prepared according to Preparation Example 1 are shown in FIG. Figure 2 It can be seen that the Li3BO3 phase is well formed as a crystal structure.

[0093] The coating-forming substance synthesized as above was pulverized into an average particle size of 0.5 μm to 0.7 μm by a bead mill to prepare a coating-forming substance having a Li 3 BO 3 component.

[0094] The properties of the coating-forming material prepared as above were tested by the following method.

[0095] The synthesized coating forming material powder was made into pellets with a diameter of 10 mm, and then heat treated at about 720° C. Then, the surface of the pellet was polished to a thickness of 0.5 mm. Au thin films were vacuum thermally deposited on both sides of the pellet with a thickness of 3 μm to form electrodes.

[0096] Then, the semicircle from 7MHz to 1Hz was measured by the two-probe method using an AC impedance analyzer. The ionic conductivity was calculated from the diameter of the measured semicircle. At this time, the calculated ionic conductivity was about 1.2x10 -6 S / cm.

[0097] Li3BO3 has a mass of 2.16 g / cm 3 Theoretical density and melting point of about 750 ° C (mp), and is composed of orthoboric acid (orthoborate, BO3 3- ) unit. In addition, it does not react with Li2O. Therefore, it does not react with the lithium byproducts present in the high-nickel positive electrode active material and can diffuse to the primary particle interface of the positive electrode active material.

[0098] (Example 1) Preparation of a large-particle positive electrode active material containing 0.005 mol of Li3BO3 and 71 mol% of Ni

[0099] 1) Preparation of positive electrode active material precursor

[0100] NiSO4.6H2O was used as a nickel raw material, CoSO4.7H2O was used as a cobalt raw material, and MnSO4.H2O was used as a manganese raw material. These raw materials were dissolved in distilled water to prepare a 2.5 M aqueous metal salt solution.

[0101] After the coprecipitation reactor was prepared, N2 was purged to prevent oxidation of metal ions during the coprecipitation reaction, and the reactor temperature was maintained at 50°C.

[0102] A metal salt aqueous solution and NH4(OH) as a chelating agent were added to the coprecipitation reactor. In addition, NaOH was used to adjust the pH. The precipitate obtained according to the coprecipitation process was filtered, washed with distilled water, and dried in an oven at 100° C. for 24 hours to prepare a positive electrode active material precursor.

[0103] The components of the prepared precursor are (Ni 0.71 Co 0.10 Mn 0.19 )(OH)2, the average particle size (D50) is 11.0μm.

[0104] 2) Preparation of positive electrode active materials

[0105] Based on 1 mol of the positive electrode active material precursor prepared in 1), 1.05 mol of LiOH·H2O (Sanquan Chemical, battery grade), 0.0022 mol of ZrO2 (Aldrich, 4N), 0.007 mol of Al(OH)3 (Aldrich, 4N), and 0.005 mol of Li3BO3 were uniformly mixed to prepare a mixture.

[0106] The mixture was placed in a tube furnace and calcined by introducing oxygen, and then cooled to room temperature.

[0107] Next, the cooled product was washed with distilled water, filtered and dried, and then H3BO3 (Aldrich) was dry mixed. The mixture was heat treated at 300° C. to 350° C. for 5 hours to prepare a positive electrode active material coated with boron (B) on the surface.

[0108] (Example 2) Preparation of a small-particle positive electrode active material containing 0.0025 mol of Li3BO3 and 71 mol% of Ni

[0109] 1) Preparation of positive electrode active material precursor

[0110] The same as 1) of Example 1, except that the average particle size (D50) of the precursor is 4 μm.

[0111] 2) Preparation of positive electrode active materials

[0112] A positive electrode active material was prepared by the same method as in 2) of Example 1 except that 0.0025 mol of Li3BO3 was added.

[0113] (Example 3) Preparation of a large-particle positive electrode active material containing 0.003 mol of Li3BO3 and 71 mol% of Ni

[0114] A positive electrode active material precursor was prepared by the same method as in Example 1 1).

[0115] Then, a positive electrode active material was prepared by the same method as in 2) of Example 1 except that 0.003 mol of Li 3 BO 3 was added.

[0116] (Example 4) Preparation of a large-particle positive electrode active material containing 0.001 mol of Li3BO3 and 71 mol% of Ni

[0117] A positive electrode active material precursor was prepared by the same method as in Example 1 1).

[0118] Then, a positive electrode active material was prepared by the same method as in 2) of Example 1 except that 0.001 mol of Li 3 BO 3 was added.

[0119] (Example 5) Preparation of a large-particle positive electrode active material containing 0.007 mol of Li3BO3 and 71 mol% of Ni

[0120] A positive electrode active material precursor was prepared by the same method as in Example 1 1).

[0121] Then, a positive electrode active material was prepared by the same method as in 2) of Example 1 except that 0.007 mol of Li 3 BO 3 was added.

[0122] (Example 6) Preparation of a large-particle positive electrode active material containing 0.01 mol of Li3BO3 and 71 mol% of Ni

[0123] A positive electrode active material precursor was prepared by the same method as in Example 1 1).

[0124] Then, a positive electrode active material was prepared by the same method as in 2) of Example 1 except that 0.01 mol of Li 3 BO 3 was added.

[0125] (Comparative Example 1) Preparation of a large-particle positive electrode active material containing 71 mol% Ni without Li3BO3

[0126] A positive electrode active material precursor was prepared by the same method as in Example 1 1).

[0127] Then, a positive electrode active material was prepared by the same method as in 2) of Example 1 except that Li 3 BO 3 was not added.

[0128] (Comparative Example 2) Preparation of a small-particle positive electrode active material containing 71 mol% Ni without Li3BO3

[0129] A positive electrode active material precursor was prepared by the same method as in Example 2, 1).

[0130] Then, a positive electrode active material was prepared by the same method as in 2) of Example 1 except that Li 3 BO 3 was not added.

[0131] (Example 7) Preparation of a small-particle positive electrode active material containing 0.0015 mol of Li3BO3 and 71 mol% of Ni

[0132] A positive electrode active material precursor was prepared by the same method as in Example 2, 1).

[0133] Then, a positive electrode active material was prepared by the same method as in 2) of Example 1 except that 0.0015 mol of Li3BO3 was added.

[0134] (Example 8) Preparation of a small-particle positive electrode active material containing 0.001 mol of Li3BO3 and 71 mol% of Ni

[0135] A positive electrode active material precursor was prepared by the same method as in Example 2, 1).

[0136] Then, a positive electrode active material was prepared by the same method as in 2) of Example 1 except that 0.001 mol of Li 3 BO 3 was added.

[0137] (Example 9) Preparation of a small-particle positive electrode active material containing 0.005 mol of Li3BO3 and 71 mol% of Ni

[0138] A positive electrode active material precursor was prepared by the same method as in Example 2, 1).

[0139] Then, a positive electrode active material was prepared by the same method as in 2) of Example 1 except that 0.005 mol of Li 3 BO 3 was added.

[0140] (Example 10) Preparation of a small-particle positive electrode active material containing 0.007 mol of Li3BO3 and 71 mol% of Ni

[0141] A positive electrode active material precursor was prepared by the same method as in Example 2, 1).

[0142] Then, a positive electrode active material was prepared by the same method as in 2) of Example 1 except that 0.007 mol of Li 3 BO 3 was added.

[0143] (Comparative Example 3) Preparation of a bimodal positive electrode active material containing 71 mol% Ni without Li3BO3

[0144] The large-particle-size positive electrode active material of Comparative Example 1 and the small-particle-size positive electrode active material of Comparative Example 2 were uniformly mixed at a weight ratio of 7:3 to prepare a bimodal positive electrode active material.

[0145] (Example 11) Preparation of a bimodal positive electrode active material containing Li3BO3 and 71 mol% Ni

[0146] The large-particle-size positive electrode active material of Example 1 and the small-particle-size positive electrode active material of Example 2 were uniformly mixed at a weight ratio of 7:3 to prepare a bimodal positive electrode active material.

[0147] (Example 12) Preparation of a large-particle positive electrode active material having a boron-containing surface layer not located on the surface of lithium metal oxide particles and containing 0.005 mol of Li3BO3 and 71 mol% of Ni

[0148] A positive electrode active material precursor was prepared by the same method as in Example 1 1).

[0149] Then, 0.005 mol of Li 3 BO 3 was added, and the positive electrode active material was prepared by the same method as 2) of Example 1 except that the dry surface coating process using H 3 BO 3 was omitted.

[0150] (Reference Example 1) Preparation of a positive electrode active material by mixing boric acid into the calcined powder after the precursor is prepared

[0151] 1) Preparation of positive electrode active material precursor

[0152] A positive electrode active material precursor was prepared by the same method as in Example 1 1).

[0153] 2) Preparation of positive electrode active materials

[0154] Based on 1 mol of the positive electrode active material precursor prepared in 1), 1.05 mol of LiOH·H2O (Sanquan Chemical, battery grade), 0.0022 mol of ZrO2 (Aldrich, 4N), and 0.007 mol of Al(OH)3 (Aldrich, 4N) were uniformly mixed to prepare a mixture.

[0155] The mixture was placed in a tube furnace and calcined by introducing oxygen, and then cooled to room temperature.

[0156] Next, the cooled product was washed with distilled water, filtered and dried, and then 0.005 mol of H3BO3 (Aldrich) was dry mixed. Then, distilled water was added for further mixing, and the amount of distilled water added was 10% by weight relative to the weight of the positive electrode active material. Subsequently, the vacuum degree was maintained below 10mTorr in a vacuum dryer and the temperature was raised to 100°C to dry out the water for the first time. Then, the temperature was raised to 190°C for the second time to finally prepare the positive electrode active material.

[0157] (Reference Example 2) Preparation of a large-particle positive electrode active material containing 0.0005 mol of Li3BO3 and 71 mol% of Ni

[0158] A positive electrode active material precursor was prepared by the same method as in Example 1 1).

[0159] Then, a positive electrode active material was prepared by the same method as in 2) of Example 1 except that 0.0005 mol of Li 3 BO 3 was added.

[0160] (Reference Example 3) Preparation of a large-particle positive electrode active material containing 0.015 mol of Li3BO3 and 71 mol% of Ni

[0161] A positive electrode active material precursor was prepared by the same method as in Example 1 1).

[0162] Then, a positive electrode active material was prepared by the same method as in 2) of Example 1 except that 0.015 mol of Li 3 BO 3 was added.

[0163] (Comparative Example 4) Preparation of a large-particle positive electrode active material containing 0.005 mol of Li3BO3 with a particle size of 1.7 μm and 71 mol% of Ni

[0164] 1) Preparation of positive electrode active material precursor

[0165] A positive electrode active material precursor was prepared by the same method as in Example 1 1).

[0166] 2) Preparation of positive electrode active materials

[0167] Based on 1 mol of the positive electrode active material precursor prepared in 1), 1.05 mol of LiOH·H2O (Sanquan Chemical, battery grade), 0.0022 mol of ZrO2 (Aldrich, 4N), 0.007 mol of Al(OH)3 (Aldrich, 4N), and 0.005 mol of Li3BO3 were uniformly mixed to prepare a mixture.

[0168] At this time, Li3BO3 was prepared by the same method as in the above-mentioned Preparation Example 1, but Li3BO3 pulverized to an average particle size of 1.7 μm was used.

[0169] The mixture was placed in a tube furnace and calcined by introducing oxygen, and then cooled to room temperature.

[0170] Next, the cooled product was washed with distilled water, filtered and dried, and then H3BO3 (Aldrich) was dry mixed. The mixture was heat treated at 300° C. to 350° C. for 5 hours to prepare a positive electrode active material coated with boron (B) on the surface.

[0171] (Experimental Example 1) Detection of primary particle surface components (electron energy loss spectroscopy, EELS)

[0172] The cross sections of the positive electrode active materials prepared in Example 1 and Comparative Example 4 were cut using FIB (focused ion beam, SEIKO 3050SE) and analyzed using STEM (scanning transmission electron microscope, JEOL ARM 200F) analysis equipment and are shown in the figure. Figure 3a , Figure 4a middle.

[0173] Next, if Figure 3a , Figure 4a As shown, the surface of the primary particles of the positive electrode active material was analyzed by EELS (electron energy loss spectroscopy, GATAN GIF Quantum ER965) equipment to analyze whether a coating containing a boron compound was formed on the surface, and the analysis results are shown in Figure 3b , Figure 4b middle.

[0174] See also Figure 3b It can be seen that lithium and boron exist on the surface of primary particles. In order to more clearly confirm whether boron is detected, Figure 3c The enlarged Figure 3b Part of the spectrum in the mid-boron detection region.

[0175] See also Figure 3c , it can be more clearly seen that boron is located on the surface of the primary particles. However, for lithium and boron, compared with the original peak position, there is a positive shift, which is usually caused by oxidation of the sample, and the positive shift is about 5-10 eV.

[0176] from Figure 3b and Figure 3c The results show that a coating layer containing a boron compound is formed on the surface of the primary particles. It can be seen from this that in the positive electrode active material according to this embodiment, a coating layer containing a boron compound is formed on the surface of the primary particles.

[0177] However, see Figure 4b It is known that, as described in Comparative Example 4, when a coating layer is formed on the surface of a lithium metal oxide using Li3BO3 having an average particle size (D50) of 1.7 μm, boron does not exist in the coating layer located on the surface of the primary particles in the positive electrode active material.

[0178] (Experimental Example 2) Analysis (SEM) of the average particle size of primary particles of the positive electrode active material

[0179] The positive active materials prepared according to Example 1 and Comparative Example 1 were subjected to SEM analysis to detect the average particle size (D50) of primary particles. Figure 5 The results of the positive electrode active material of Comparative Example 1 are shown in FIG. Figure 6 The results of the positive electrode active material of Example 1 are shown in FIG.

[0180] See also Figure 5 It can be seen that in the positive electrode active material prepared according to Comparative Example 1, the average particle size (D50) of the primary particles is about 0.2 μm to 1 μm.

[0181] On the other hand, see Figure 6 It can be seen that in the positive electrode active material prepared according to Example 1, the average particle diameter (D50) of the primary particles increases to 0.5 μm to 1.3 μm.

[0182] That is, when preparing the positive electrode active material, if Li3BO3 is mixed with the metal precursor and the lithium raw material and then calcined, Li3BO3 will act as a sintering agent. In this way, when the average particle size (D50) of the primary particles prepared at the same calcination temperature increases, it is not only very advantageous in reducing energy costs, but also the crystallinity of the secondary particles increases. In this way, when the crystallinity increases, it is conducive to the deintercalation / intercalation of lithium ions, and the life characteristics can be improved. In addition, the residual lithium content on the surface of the positive electrode active material can be reduced, so it is very advantageous.

[0183] (Experimental Example 3) Evaluation of X-ray Diffraction

[0184] For the positive active materials prepared according to Examples 1 to 2 and Comparative Examples 1 to 2, the unit cell constant was measured by X-ray diffraction measurement using CuKα rays. The measured a-axis length and c-axis length and the distance ratio between the crystal axis (c / a-axis ratio) are shown in Table 1 below.

[0185] In addition, the Full Width at Half Maximum and the crystalline size of the positive electrode active material were measured and shown in Table 1 below.

[0186] For crystallographic investigation, Rietveld analysis was performed using high score plus Rietveld software. XRD detection for Rietveld analysis was performed using CuKα radiation as the target radiation and XRD equipment from X′Pert powder (PANalytical) was used for detection. Detection was performed under the detection conditions of 2θ=10° to 110° and scanning speed (° / S)=0.328 to obtain the intensities of the (003) plane, (104) plane, (006) plane, (102) plane, and (101) plane.

[0187] I(003) / I(104) was determined from the intensity (peak area) detection results of the (003) plane and the (104) plane and is shown in Table 1 below.

[0188] In addition, the R-factor was calculated from the intensity measurement results of the (006) plane, the (102) plane, and the (101) plane according to the following formula 1 and is shown in the following Table 1.

[0189] In this result, the GOF (goodness of fit) value was calculated to be within 1.3, so the Rietveld structure analysis result can be considered to be reliable data.

[0190] [Formula 1]

[0191] R-factor={I(006)+I(102)} / I(101)

[0192]

Table 1

[0193]

[0194]

[0195] Referring to Table 1, when comparing Example 1 and Comparative Example 1 of large-particle positive electrode active materials, the lengths of the a-axis and c-axis do not change much. However, compared to Comparative Example 1, the full width at half maximum of Example 1 is significantly reduced, and the grain size is greatly increased. This shows that crystallization is better at the same calcination temperature. When such a well-crystallized positive electrode active material is applied to a lithium secondary battery, the life characteristics of the battery can be improved, and residual lithium can be reduced, so it is very beneficial.

[0196] Next, Li was detected by the peak area ratio of I(003) / I(104) between I(003) and I(104). + and Ni 2+ In addition, the R-factor value, which can be used to determine the degree of hexagonal order, is obtained using Formula 1.

[0197] Compared with Comparative Example 1, the I(003) / I(104) ratio of the positive electrode active material of Example 1 increases, the R-factor decreases, and thus cation mixing decreases, and the hexagonal structure also grows well.

[0198] On the other hand, when comparing Example 2 and Comparative Example 2 of the small particle size positive electrode active material, the lengths of the a-axis and c-axis do not change much. However, like the large particle size active material, the half peak width is greatly reduced and the grain size is increased.

[0199] (Experimental Example 4) Detection of particle strength

[0200] The particle strength of the positive electrode active materials prepared according to Example 1 and Comparative Example 1 was tested using a device (Micro Particle Compression Tester, MCT-W500 manufactured by Shimadzu Corporation) equipped with an optical microscope and a compression rod for compression.

[0201] Specifically, for particle strength, 15 positive electrode active material particles were randomly selected for testing, and the maximum value, minimum value and interference were removed and shown in Figure 7 and Figure 8 middle.

[0202] Figure 7 is the particle strength test result of the positive electrode active material of Example 1, Figure 8 This is the particle strength test result of the positive electrode active material of Comparative Example 1.

[0203] See also Figure 7 , the positive electrode active material of Example 1 showed a particle strength of about 180 MPa. Figure 8 , the positive electrode active material of Comparative Example 1 showed a particle strength of about 150 MPa. It can be seen that if the positive electrode active material contains Li3BO3, the particle strength of the positive electrode active material will increase when calcined at the same temperature. When the particle strength of the positive electrode active material increases, cracks are suppressed during the charging and discharging of the lithium secondary battery, thereby suppressing side reactions with the electrolyte.

[0204] By the same method, the particle strength of the positive electrode active materials prepared according to Examples 1, 3, 4, 5, 6 and Comparative Example 1 was tested, and the particle strength calculated according to Formula 2 is shown in Table 2 below.

[0205] [Formula 2]

[0206] St=2.8×P / (πd 2 )

[0207] St: Particle strength (tensile strength (MPa))

[0208] P: Applied pressure (test force (N))

[0209] D: particle diameter (mm)

[0210] (Experimental Example 5) Evaluation of electrochemical characteristics

[0211] Electrochemical evaluation was performed after preparing 2032 coin-type half cells using the positive electrode active materials prepared according to Examples 1 to 12, Comparative Examples 1 to 4, and Reference Examples 1 to 3.

[0212] (1) Preparation of coin-type half-cell

[0213] Specifically, the positive electrode active material, polyvinylidene fluoride binder (trade name: KF1100) and Denka black conductive material are mixed in a weight ratio of 92.5:3.5:4, and the mixture is added to N-methyl-2-pyrrolidone (N-Methyl-2-pyrrolidone) solvent, and the solid content in the solvent reaches about 30 weight % to prepare a slurry of the positive electrode active material.

[0214] The slurry was coated on an aluminum foil (Alfoil, thickness: 15 μm) as a positive electrode collector using a doctor blade, and then pressed after drying to prepare a positive electrode. The positive electrode loading was about 14 mg / cm 2 , the compression density is about 3.1g / cm 3 .

[0215] A 2032 coin-type half-cell was prepared by conventional methods using the positive electrode, a lithium metal negative electrode (thickness of 200 μm, Honzo metal), an electrolyte and a polypropylene separator. The electrolyte was prepared by dissolving 1M LiPF6 in a mixed solvent of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate (EMC) (mixing ratio of EC: DMC: EMC = 3: 4: 3 volume %), and adding 1.5 wt% of vinylene carbonate (VC) thereto.

[0216] (2) Evaluation of charge and discharge characteristics

[0217] The coin-type half-cell prepared in (1) was aged at room temperature (25° C.) for 10 hours and then subjected to a charge and discharge test.

[0218] For capacity evaluation, 170 mAh / g was used as the reference capacity at a rate of 0.1C, and the charge and discharge conditions were constant current (CC) / constant voltage (CV) 3V to 4.3V, 1 / 20C cut-off conditions. For the initial capacity, a charge and discharge was performed once at 0.1C charge / 0.1C discharge, and after the discharge capacity was detected, the result was shown in Table 2 below as the discharge capacity.

[0219] In addition, the ratio of the 0.2C discharge capacity to the 0.2C charge capacity was determined, and the results are shown in Table 2 below as initial efficiency.

[0220] on the other hand, Fig. 9 Graphs comparing initial charge and discharge after charging and discharging are shown for the positive electrode active materials of Example 1 and Comparative Example 1 when the charge voltage is increased to 4.5 V.

[0221] More specifically, Fig. 9It is used to more clearly confirm the effect of adding Li3BO3 together with the metal precursor and the lithium raw material to prepare the positive electrode active material. That is, Fig. 9 A graph comparing initial charge and discharge after increasing the charge voltage to 4.5 V, which is higher than a general detection range of 4.3 V, for the positive electrode active materials of Example 1 and Comparative Example 1 and performing one charge and discharge at 0.1 C charge / 0.1 C discharge conditions is shown.

[0222] See also Fig. 9 , Comparative Example 1 showed a charge capacity of 230 mAh / g and a discharge capacity of 207 mAh / g. On the other hand, the charge capacity of Example 1 was 236 mAh / g and the discharge capacity was 212 mAh / g, and it can be confirmed that both the initial charge and discharge capacities increased. In particular, during charging in the 3.9 V to 4.2 V region, the resistance of the positive electrode active material of Example 1 was smaller than that of the positive electrode active material of Comparative Example 1.

[0223] For 2C output, the discharge capacity is detected by applying a constant current twice that of the 1C reference capacity, which is converted into a 2C / 0.1C capacity ratio in the range of 4.3V-3V.

[0224] Next, in order to confirm the high temperature life characteristics, 50 charge and discharge cycles were performed at high temperature (45°C) under 0.3C charge / 0.3C discharge conditions to find the ratio of 50 discharge capacities to 1 discharge capacity. The results are shown in Table 2 below. On the other hand, for the positive electrode active materials of Example 1 and Comparative Example 1, Fig.10 A graph comparing high temperature life characteristics is shown in FIG.

[0225] See also Fig.10 It can be confirmed that the positive electrode active material of Example 1 retains 99% of the initial capacity after 50 charge and discharge cycles, showing a very excellent result. On the other hand, the positive electrode active material of Comparative Example 1 retains about 96% of the capacity after 50 charge and discharge cycles, indicating that the life characteristics have decreased.

[0226] In addition, the increase rate of high temperature resistance (direct current internal resistance: DC-IR (Direct Current Internal Resistance)) was calculated as follows: after measuring the initial resistance value at high temperature, the resistance value after 50 cycles was measured, and the increase rate was converted into percentage (%). The results are shown in Table 2 below.

[0227] At this time, the high temperature initial resistance value was obtained by applying a 0.5C discharge current to the battery at 45°C from a 4.3V 100% charged state and measuring the voltage value after 60 seconds, thereby obtaining the resistance value using Ohm's law (R=V / I).

[0228] On the other hand, for the positive electrode active materials of Example 1 and Comparative Example 1, Fig.11 A graph comparing the high temperature resistance increase rate is shown in FIG.

[0229] See also Fig.11 The positive electrode active material of Comparative Example 1 showed a resistance increase rate of 70% relative to the initial resistance after 50 charge and discharge cycles at high temperature (45°C). On the other hand, the positive electrode active material of Example 1 still showed a resistance increase rate of about 40% after 50 charge and discharge cycles, which was about 30% lower than that of the positive electrode active material of Comparative Example 1. Therefore, it also showed a very excellent result in terms of resistance increase rate.

[0230]

Table 2

[0231]

[0232]

[0233] Referring to Table 2, in the case of the large-particle positive electrode active materials prepared according to Examples 1, 3 to 6 and 12, in which a coating containing a boron compound is formed on the surface of the primary particles, the particle strength is greatly improved compared to Comparative Example 1 in which a coating containing a boron compound is not formed on the surface of the primary particles. In addition, the initial efficiency, 2C output, capacity retention rate and high-temperature resistance increase rate are all improved.

[0234] However, in the positive electrode active material having large particles, even if a coating containing a boron compound is formed on the surface of the primary particles, in the case of the positive electrode active materials prepared according to Reference Examples 2 and 3 in which the content of the boron compound contained in the secondary particles exceeds the range of 0.001 mol to 0.01 mol, although the electrochemical characteristics such as output characteristics, capacity retention rate and high-temperature resistance characteristics are better than those of Comparative Example 1, the electrochemical characteristics are slightly worse than those of the embodiments.

[0235] In addition, compared with Comparative Example 2 in which a coating containing a boron compound is not formed on the surface of the primary particles, the small-particle positive electrode active materials prepared according to Examples 2 and Examples 7 to 10 in which a coating containing a boron compound is formed on the surface of the primary particles also have improved initial efficiency, 2C output, capacity retention rate and high-temperature resistance increase rate.

[0236] At the same time, in the case of Example 11 and Comparative Example 3 in which the positive electrode active materials were prepared in a bimodal form, the positive electrode active material of Example 11 having a coating layer containing a boron compound formed on the surface of the primary particles also had superior electrochemical characteristics than Comparative Example 3 in which no coating layer was formed.

[0237] On the other hand, unlike the embodiment in which the positive electrode active material is prepared by mixing the coating-forming material after preparing the precursor and then calcining it, in the case of Reference Example 1 in which the positive electrode active material is prepared by mixing boric acid after preparing the calcined powder, the particle strength is significantly lower, and the electrochemical properties, especially the high-temperature resistance, are significantly increased, resulting in extremely poor battery performance.

[0238] Secondly, in the case of Comparative Example 4 in which the positive electrode active material was prepared using a coating-forming material having an average particle size (D50) of 1.7 μm for Li3BO3, the particle strength was significantly low, and the electrochemical characteristics such as output characteristics, capacity retention rate and high-temperature resistance characteristics were also extremely poor.

[0239] Therefore, as shown in this embodiment, the positive electrode active material having a coating layer containing a boron compound formed on the surface of the primary particles can greatly improve the battery performance in any form of large particle size, small particle size and bimodal.

[0240] (Experimental Example 6) TEM structure analysis

[0241] The surface of the primary particles of the positive electrode active material prepared according to Example 1 was subjected to TEM structural analysis, and the results are shown in Fig.12a The TEM structural analysis is to analyze the crystallinity using a spherical aberration corrected transmission electron microscope (Cs-Corrected Transmission Electron Microscopy, JEOL, JEM-ARM200F, x20K, 200kV).

[0242] To take a closer look, Figure 12b The enlarged Fig.12a The region where primary particles of the positive electrode active material and the coating on the surface of the primary particles coexist. Figure 12b , certain oblique line patterns such as comb lines were observed in the primary particle region (i.e., active material region), which confirmed that the layered crystal structure was present. On the other hand, the coating layer (i.e., coating region) on the primary particle surface was a random pattern without a certain pattern, which confirmed that the amorphous structure was present.

[0243] The present invention can be implemented in various different ways and is not limited to the above-mentioned embodiments. It will be appreciated by those skilled in the art that the present invention can be implemented in other specific ways without changing the technical concept or essential features of the present invention. Therefore, the above-mentioned embodiments are exemplary in all aspects and are not restrictive.

Claims

1. A positive electrode active material, which is a lithium metal oxide particle in the form of a secondary particle comprising a primary particle, a coating containing a boron compound is located on at least a portion of the surface of the primary particle, the boron compound comprising an amorphous structure, The content of the boron compound in the secondary particles is 0.001 mol to 0.007 mol, The porosity of the lithium metal oxide particles represented by the following formula 1 is 0.4% to 6%, and The particle strength of the lithium metal oxide particles is 151 MPa to 200 MPa, [Formula 1] Porosity = (pore area of ​​lithium metal oxide particle cross section A / area of ​​lithium metal oxide particle cross section A) × 100% In Formula 1, A represents the area of ​​a cross section having a diameter of a lithium metal oxide particle.

2. The positive electrode active material according to claim 1, wherein The boron compound contains Li and B.

3. The positive electrode active material according to claim 1, wherein At least a portion of the primary particles including the boron compound are located inside the lithium metal oxide particles.

4. The positive electrode active material according to claim 1, wherein Compared with the case where the coating layer containing the boron compound is not located on at least a portion of the surface of the primary particles at the same temperature, the average particle size D50 of the primary particles increases by 1.3 to 2.5 times.

5. The positive electrode active material according to claim 4, wherein The average particle size D50 of the primary particles is 0.3 μm to 2 μm.

6. The positive electrode active material according to claim 1, wherein The lithium metal oxide particles are plural and are at least one of large particles having an average particle size D50 of 10 μm to 30 μm, small particles having an average particle size D50 of 1 μm to 6 μm, and bimodal particles in which the large particles and the small particles are mixed.

7. The positive electrode active material according to claim 6, wherein The half maximum width (FWHM) of the diffraction peak of the (110) plane of the large particle based on X-ray diffraction (110) 0.14° to 0.18°, The half maximum width (FWHM) of the diffraction peak of the (110) plane of the small particle based on X-ray diffraction (110) 0.15° to 0.19°.

8. The positive electrode active material according to claim 1, wherein The boron compound includes Li3BO3, LiBO2, Li3B3O5, Li6B4O9, Li 6.52 B 18 O 0.7 , Li 7.4 B 18 O 0.7 , Li 7.8 B 18 O 0.9 and at least one of Li2B4O7.

9. The positive electrode active material according to claim 1, wherein The content of nickel in the metal in the secondary particles is 0.65 mol to 0.99 mol.

10. The positive electrode active material according to claim 1, wherein The lithium metal oxide further includes at least one of Al and Zr in the secondary particles.

11. The positive electrode active material according to claim 1, further comprising: The surface layer is located on the surface of the lithium metal oxide particles.

12. The positive electrode active material according to claim 11, wherein The surface layer contains one or more selected from the group consisting of B, Zr, Al, W, Nb, P, Ce, Ti, Ta, Co, Si and Mn.

13. A method for preparing a positive electrode active material, comprising: a step of preparing a coating-forming substance containing a boron compound; A step of adding a metal salt aqueous solution into a coprecipitation reactor to obtain a metal precursor; and a step of mixing the coating-forming substance, the metal precursor and a lithium raw material and calcining them to obtain a positive electrode active material containing lithium metal oxide particles, The coating forming material is provided in the form of micro-particle powder. wherein in the step of mixing the coating-forming substance, the metal precursor and the lithium raw material and then calcining them to obtain the positive electrode active material, the coating-forming substance is mixed into secondary particles so that the content of the boron compound is 0.001 mol to 0.007 mol, and The porosity of the lithium metal oxide particles represented by the following formula 1 is 0.4% to 6%, and The particle strength of the lithium metal oxide particles is 151 MPa to 200 MPa, [Formula 1] Porosity = (pore area of ​​lithium metal oxide particle cross section A / area of ​​lithium metal oxide particle cross section A) × 100% In Formula 1, A represents the area of ​​a cross section having a diameter of a lithium metal oxide particle.

14. The method for preparing a positive electrode active material according to claim 13, wherein: The average particle size of the microparticle powder is 0.1 μm to 1.5 μm.

15. The method for preparing a positive electrode active material according to claim 13, wherein: The step of preparing a coating-forming substance containing a boron compound comprises: A step of mixing raw materials constituting the boron compound and then calcining the mixture; and The step of pulverizing the calcined product after the calcination.

16. The method for preparing a positive electrode active material according to claim 13, wherein: The step of obtaining the positive electrode active material comprises: The step of mixing the coating forming substance, the metal precursor and the lithium raw material substance and then calcining to prepare a calcined body; and A step of forming a surface layer on the surface of the calcined body.

17. A lithium secondary battery comprising: A positive electrode comprising the positive electrode active material according to any one of claims 1 to 12; a negative electrode comprising a negative electrode active material; and An electrolyte is located between the positive electrode and the negative electrode.

Citation Information

Patent Citations

  • Bimodal lithium transition metal based oxide powder for use in a rechargeable battery

    KR1020150092258A

  • KR20190013674A

  • KR20190079526A